Cell therapy products: focus on issues with manufacturing and quality control of chimeric antigen receptor T‐cell therapies. Issue 4 (19th November 2018) - Eyles, Jim E; Vessillier, Sandrine; Jones, Anika; Stacey, Glyn; Schneider, Christian K; Price, Jack
Abstract: Recent accelerated approvals of Chimeric Antigen Receptor T‐cell (CAR‐T) therapies targeting refractory haematological malignancies underscore the potential for this novel technology platform to provide new therapeutic options for oncology areas with high unmet medical needs. However, these powerful 'living drugs' are markedly different to conventional small molecule and biologic therapies on several levels. The highly complex nature and varied composition of CAR‐T based products still requires considerable investigation to resolve the best approaches to ensure reproducible and cost‐effective manufacture, clinical development, and application. This review will focus on key issues for manufacturing and quality control of these exciting new therapeutic modalities, preceded by a brief description of CAR principals and clinical development considerations. © 2018 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.